2021
DOI: 10.25083/rbl/26.1/2323.2330
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of mollars with MOD cavities restored with different materials

Abstract: Restoring teeth with second class cavities is a challenge in dentistry. Both the carious process and the preparation of the cavity for the dental restoration reduces the tooth resistance to the masticatory forces. It has been shown that modern aesthetic materials using an adhesive system improve the stress resistance of the restored teeth. There is a series of studies that attempted to determine the type of optimal material that would provide increased resistance to occlusal demands. In the present study we tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of the current investigation were consistent with that of Margarit et al [44], who found that teeth treated with ormocer had the highest µTBS value, followed by those restored with nano-filled composite, and finally those restored with microhybrid resin composite. But in the study of Dina et al [45], they compared the µTBS of some MOD cavities in premolars that had been filled with various materials (ormocer, nano-filled, nanoceramic, and microhybrid composite), and they found that the teeth restored with nanoceramic composite had the best mean value of µTBS.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current investigation were consistent with that of Margarit et al [44], who found that teeth treated with ormocer had the highest µTBS value, followed by those restored with nano-filled composite, and finally those restored with microhybrid resin composite. But in the study of Dina et al [45], they compared the µTBS of some MOD cavities in premolars that had been filled with various materials (ormocer, nano-filled, nanoceramic, and microhybrid composite), and they found that the teeth restored with nanoceramic composite had the best mean value of µTBS.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study were in concurrence with the results of Taha et al (25) who observed that improved fracture resistance with nearly similar values to the positive control group was found in the nanoceramic group while microhybrid group revealed significantly lower fracture resistance in comparison to all restored groups, that was also statistically insignificant when compared to the negative control group. Also Mărgărit et al (26) reported that microhybrid composite showed the lowest fracture resistance values compared to other restorative materials used in their study and was insignificantly higher that negative control group.…”
Section: Discussionmentioning
confidence: 77%
“…Fractures of posterior teeth with mesial-occlusal-distal (MOD) cavities restored with different materials can occur in mastication more frequently than those of healthy ones, proportionally with the quantity of hard dental tissues loss [ 1 , 2 , 3 ]. As restoration materials, those that adhere most to the dentin are the most recommended [ 4 ], considering that using them increases the resistance of the restored tooth [ 5 , 6 ]. A material used as a base for replacing lost dentine in a medium-sized cavity ensures a uniformly distributed load and tension across the filled tooth [ 7 ], especially in MOD cavities [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%